PEDAGOGICAL CHARACTERISTICS OF THE GENDER ANALYSIS OF GAMES - Kholmatova Ergashoy Salimjon qizi (Innovate Conferences, 2025)
This article examines the concepts of intangible culture and the history of their study. Since ancient times, the culture of the peoples of Central Asia has been formed and developed in conjunction with each other; on the other hand, it has been influenced by the culture of the peoples of neighboring countries and regions, and vice versa. Folk games occupy a central place in the system of national values inherent in the ancient layer of spiritual heritage. Since Uzbekistan is one of the most densely populated regions of Central Asia, one of the pressing issues is to study the dynamics of the ethnostructure of the population, its ethnic composition, language and customs. Therefore, certain aspects of the problem have attracted the attention of many historians, ethnographers, archaeologists, anthropologists, literary scholars, and linguists.
Keywords: Intangible culture, spiritual heritage, national values, folk games, ethnic composition of the population, customs, economic life, Ramadan songs.